Características sociodemográficas e fatores de risco para o câncer de próstata na atenção básica - Czorny, Rildo César Nunes (2017)
Objectives: To describe the profile of the male patient in a Primary Family Health Unit and identify risk factors for prostate cancer. Method: This is a descriptive, cross-sectional study, of quantitative approach developed in a Primary Family Health Unit integrated into the networkservice of the Unified Health System. The study sample comprised 150 male users who have been attended this unit for consultation and / or nursing reception in the month of November / 2015. Results: The majority of patients evaluated were between 61 and 80 years old (48 ¬- 32.00%); they were considered whites (91 - 60.67%), with a fundamental level of education (75 - 50.00%), with Monthly income of 2 to 3 minimum wages (55 - 36.67%). The majority of the patients were classified as sedentary (114 - 76.00%), ingesting alcohol (84 - 56.00%) up to twice a week (53 - 63.10%) and not smoking and Or use of inhaled drugs (113 - 75.33%). The majority of patients reported eating red (133-88.67%), milk (96-64.00%), fat (76-50.67%), fruits (115-76.67%), vegetables - 82.00%) and legumes (129 - 86.00%) five or more times per week, 23.33% had a history of prostate cancer (father or brother). The data indicated that the patients presented chronic diseases (82 - 54.67%), the main one being Systemic Hypertension (35 - 42.68%), followed by diabetes and Systemic Hypertension (20 - 34.39%), Diabetes (14 - 14.63%), and others (15-18.29%). Specific prostate antigen was the most frequent (84 - 56.00%) followed by rectal (48 - 32.00%), ultrasound (16 - 10.67%) and biopsy (12 - 8.00 %). Conclusions: Need for new strategies to sensitize younger men to seek care in the pursuit of disease prevention and health promotion. The main factors for prostate cancer reported by participants were age, schooling, sedentary lifestyle, use of alcoholic beverage, red meat intake, milk and milk products, fat and overweight. The present study suggests that the male population needs to be assisted according to the guidelines of the National Policy for Integral Attention to Human Health, and there may be a protocol of care with actions necessary for the knowledge of the situation and the impact on the morbidity and mortality profile aimed at This clientele.